DRIVING AI ADOPTION AMONG ACCOUNTING STUDENTS: THE ROLE OF TECHNOLOGY READINESS, DIGITAL COMPETENCE, AND LEARNING ENVIRONMENT - Budi Septiawan; Muhamad Ichsan Rauf; Alena Layla Sholaha; Aura Reksa Kinasih; Gita Airindika Priastutik (JITTER: Jurnal Ilmiah Teknologi dan Komputer, 2026)
The rapid development of artificial intelligence (AI) has brought significant transformation across various sectors, including higher education. This study analyzes the factors influencing AI adoption among university students, focusing on technological readiness, digital competence, and the learning environment. Through a quantitative approach and analysis using Structural Equation Modeling - Partial Least Squares (SEM-PLS), this research finds that digital competence and the learning environment have a positive and significant influence on AI adoption. Conversely, technological readiness does not show a significant influence. These findings provide practical contributions by offering insights for educational institutions to design effective strategies in enhancing AI literacy and integration. Theoretically, this research enriches the literature on educational technology adoption focusing on the context of AI usage.